Arquitetura de repositório semântico de dados para organização de pesquisa agropecuária - Gomes, Francisco Carlos da Rocha (2013)
Within organizations, knowledge management, with its processes of acquisition, storage and sharing, based on information resources intended for direct use by humans. However, combining these resources are not enough to be used or reused to produce new knowledge or emerging innovation. In todays scenario of increasing the amount of information recorded and the challenge of understanding more and better the complexity of the phenomena, it is necessary to have some form of organizational memory integrated and inclusive, so meet the needs of users in different perspectives, situations, dimensions, conditions and contexts. In contrast, the Semantic Web technology manifests features that enable the development of a semantic repository architecture that meets these demands. In this sense, this paper aims to outline a semantic repository architecture that integrates enterprise data and can serve as a reference implementation in agricultural research institution